FAKTOR – FAKTOR PENGHAMBAT YANG DIALAMI OLEH MAHASISWA PENDIDIKAN EKONOMI UNIVERSITAS RIAU DALAM MELAKUKAN SISTEM PERKULIAHAN DARING PADA MASA PANDEMI COVID 19 - Darliza, Darliza; Suarman, Suarman; Syabrus, Hardisem (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract : This research was motivated by the existences of factors that prevented economic education students from carrying out online lectures during the covid – 19 pandemic. This study aims to determine the factors that hinder students of economic education in carrying out online lectures. For samples taken as many as 60 people. Date were cpllected using an open questionnaire and then analyzed using quantitative techniques witha sample statistical approach. Based on the research, the results show that online lectures have inhibiting factors that the implementation of online lecturesin the economic side, the IT capability side, the time provided and the policy of using google classroom at UNRI.Key Words: Online Lectures, Econom, IT, Time, And Google Classrom